Pengembangan Media Literasi Digital “LOTIKA” Berbasis Android dalam Meningkatkan Kemampuan Pemahaman Konsep Matematika Mahasiswa - R, Nurmala; Maulina, Hikma (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
This research is research and development (Research and Development) which aims to produce a product in the form of android-based digital literacy media "Lotika" in improving students' ability to understand mathematical concepts. The development of this media refers to the Luther model. This model consists of 6 stages of development namely Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The instruments used to collect data in development research these are documentation, observation, assessment sheets, questionnaires and concept understanding tests. Documentation and observation is carried out to find out potential problems and initial analysis of product design. The assessment sheet is used to determine the feasibility of teaching material products that have been developed from the responses of experts. While the questionnaire is used to determine the practicality of the product that has been developed and has been validated by experts. While the concept understanding ability test is used to see whether there is an increase in conceptual understanding ability after using the media. The results of the analysis of the validator's assessment on the media aspect obtained an average score of 3.38 and on the media spec 3.44 so that these two aspects are in the very good category. For the results of user response data, an average score was obtained in the small group product trial of 3.75 and in the field test 3.48 so that the two trials were in the very good category. While the results of measuring the ability to understand concepts obtained an N-Gain of 0.31 which is in the medium category. Based on the results of this analysis, it can be concluded that the products that have been developed and have been tested can be used in the learning process. The products developed are stated to be valid and practical to use and these products can improve students' ability to understand mathematical concepts in understanding mathematical logic material in the moderate category.